Karakteristik Mutu Sensori, Sifat Fisik, dan Aktivitas Antioksidan Sediaan Lip Balm Fortifikasi Chlorella vulgaris - Dian Iriani; Khairani Putri; Tjipto Leksono (Universitas Teuku Umar, 2026)
Lip balm is a cosmetic preparation designed to maintain lip moisture and protect the lips from environmental exposure. The use of natural ingredients, including the microalga Chlorella vulgaris, which is rich in bioactive compounds and has potential as a natural antioxidant, continues to attract research interest. This research sought to evaluate the effect of Chlorella vulgaris microalgae powder addition on the sensory quality, physical properties, and antioxidant activity of lip balm formulations, as well as to determine the optimal concentration.The study employed an experimental method using a non-factorial Completely Randomized Design with 4 concentrations of Chlorella vulgaris powder: LB0 0%, LB1 1%, LB2 3%, and LB3 5%. The evaluated parameters included sensory attributes (appearance, texture, and aroma), physical properties (homogeneity, pH, melting point, spreadability, and loss on drying), and antioxidant activity using the FRAP method. The results indicated that the addition of Chlorella vulgaris powder significantly affected the characteristics of the lip balm. The LB1 treatment (1% concentration) was identified as the best formulation, providing optimal sensory acceptance (6.84, 7.91, 8.44) favorable physical properties (homogeneous, 5.37, 52°C, even spreadability, 5%), and antioxidant activity with an IC50 value of 605.55 μg/mL. Therefore, Chlorella vulgaris microalgae powder has potential to be utilized as a natural active ingredient in lip balm formulations.